Morphology of Tissues During Intraoperative Stretching in The Plastic of Scar Deformities of The Lips (Texas Journal of Medical Science, 2024)
Post-burn scarring of the lips often causes functional disorders. Intraoperative balloon stretching of tissues as a method of reconstructive surgery is widely used in surgical rehabilitation of this category of patients. However, structural changes in tissues during balloon stretching have not been sufficiently studied. Using light-optical and electron microscopy, samples of various areas of intact lip skin subjected to stretching during surgery in order to obtain a skin resource for plastic surgery were studied. It has been shown that stretching does not lead to significant violations of the skin structure